2020
DOI: 10.1136/flgastro-2019-101350
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow dyspoiesis associated with severe refractory anaemia in liver cirrhosis

Abstract: Background and aimPeripheral cytopaenias and dyspoiesis are common in cirrhosis; however, the prevalence of dyspoiesis and its contribution in cirrhosis-related cytopaenias has not been studied. We aimed to study the bone marrow (BM) dyspoiesis and its impact on peripheral blood cell counts and refractory anaemia in patients with cirrhosis.Patients and methodsWe reviewed all the BM aspirates and biopsies of cirrhotic cases, done from 2011 to 2018 for clinical indications. Dyspoiesis was considered if >5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…Since we included only patients with peripheral blood cytopenia, the frequency and severity of peripheral blood cytopenias in our cohort were higher than those reported in studies that included all patients with advanced liver cirrhosis [ 24 ]. In agreement with our findings, the limited number of available reports on bone marrow assessment in patients with liver cirrhosis likewise identified non-specific or reactive changes that did not meet diagnostic criteria for primary bone marrow pathologies in most cases [ 25 , 26 , 27 , 28 ]. To our knowledge, our study is the first to report results of a comprehensive, combined cytologic, histologic and immunologic bone marrow assessment in patients with liver cirrhosis and peripheral blood cytopenia.…”
Section: Discussionsupporting
confidence: 91%
“…Since we included only patients with peripheral blood cytopenia, the frequency and severity of peripheral blood cytopenias in our cohort were higher than those reported in studies that included all patients with advanced liver cirrhosis [ 24 ]. In agreement with our findings, the limited number of available reports on bone marrow assessment in patients with liver cirrhosis likewise identified non-specific or reactive changes that did not meet diagnostic criteria for primary bone marrow pathologies in most cases [ 25 , 26 , 27 , 28 ]. To our knowledge, our study is the first to report results of a comprehensive, combined cytologic, histologic and immunologic bone marrow assessment in patients with liver cirrhosis and peripheral blood cytopenia.…”
Section: Discussionsupporting
confidence: 91%
“…BM examination was performed as per the clinical indications, i.e., cytopenia, pyrexia of unknown origin, and dyserythropoiesis in refractory anemia as described in our previous study. 6 Clinical indications were similar across the Child-Turcott-Pugh (CTP) classes ( Supplementary Table 1 ). In these cirrhosis patients, the major etiology was ethanol-related, followed by viral, nonalcoholic steatohepatitis, and cryptogenic.…”
Section: Methodsmentioning
confidence: 97%
“…Study group: The study included cirrhotic patients who underwent clinically indicated bone marrow (BM) examinations from Jan 2017 -June 2019 at the Institute of Liver and Biliary Sciences, New Delhi (n=127). BM examination was done as per the clinical indications {(i.e., cytopenia, pyrexia of unknown origin, and dyserythropoiesis in refractory anemia in our previous study [13]}. The clinical indications across the CTP A, B, and C categories were similar [Table S1].…”
Section: Phase-1 Study Participants and Methodsmentioning
confidence: 99%